Hubungan Antara Konsep Diri Dengan Kecerdasan Emosional Peserta Didik Kelas XI SMA N 1 Babakan - Karina Rachmawati; Handayani, Arri; Venty (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to determine the relationship between self-concept and emotional intelligence in class XI students of SMA N 1 Babakan. The background of this study is the importance of a positive self-concept in supporting students' emotional intelligence, which ultimately has an impact on their achievement and well-being. The research method used is quantitative with a correlational approach. The sample of this study consisted of 59 students taken from a population of 395 students in class XI through a purposive sampling technique of 15%. The data collection technique used a questionnaire with a Likert scale, which was tested for reliability using Cronbach's Alpha and obtained results of 0.894 for the self-concept instrument and 0.831 for emotional intelligence, both of which were declared reliable. Data analysis was carried out using normality test, linearity test, and hypothesis testing with Pearson Product Moment correlation method processed through SPSS software version 26. The results of hypothesis testing show that there is a significant relationship between self-concept and emotional intelligence, with sig. (2-tailed) <0.05 and the correlation coefficient is positive. This shows that the better the self-concept of students, the higher the emotional intelligence they have. This study indicates that there is a relationship between self-concept and emotional intelligence in class XI students of SMA N 1 Babakan.